Biodiversity in agriculture : domestication, evolution, and sustainability - Harlan, Jack R. (Jack Rodney); Gepts, Paul L.; University of California, Davis. (Cambridge ; New York : Cambridge University Press, 2012)
Includes bibliographical references and index.